KEDUDUKAN ANAK ANGKAT DALAM PEMBAGIAN WARIS MENURUT HUKUM POSITIF (PENGADILAN AGAMA TENGGARONG) - Dessy Puspitasari (Journal of Law ( Jurnal Ilmu Hukum ), 2021)
ABSTRACT An appointment is an important event that occurs in human life. This event has a legal impact on the prospective adoptive parents, adopted children, and their families. Therefore it must be decided through mature thinking by considering all legal consequences and consequences that will arise from the decision to appoint the child.This study is empirical normative law research that is a form of research based on or sourced from literature such as books, documents, legislation, and scientific works related to the title and main problems in this writing. The research procedures used are Library Studies, Field Studies, and Data Processing. Then analyzed qualitatively by describing and describing the data and facts produced from a study in the field with an interpretation, evaluation, and general knowledge to draw conclusions that are specific to submit suggestions, as well as processed data.From the results of research that has been done and analyzed the position of adopted children in the distribution of inheritance according to positive law is permitted to receive part of the inheritance of their adoptive parents through a will grant or obligatory will. The solution to the distribution of inheritance to adopted children according to positive law with a will is obligatory with provisions not exceeding 1/3 of inheritance, but in reality, this 1/3 part is too large, so in reality adopted children or adoptive parents only get part 1 / 10 to 1/8, because part 1/3 exceeds the share of experts who have a closer or more rightful relationship, such as a wife who only obtains 1/4 of inheritance if she does not have children and a mother who only gets 1 / 6 of inheritance.  Keywords: adopted children, inheritance, and grants